Constraints of Domestic Water Management in the Rural Areas of the Oases of South-Eastern Morocco: A Case Study (Journal of Libya for geographical studies, 2022)
The importance of the study is justified by the problems faced by domestic water management in rural areas in oasis cases, which intensified in the first and second decades in the twentieth century, due to the social, cultural and economic transformations that these cases witnessed. Therefore, this study aims to evaluate the extent of the balance of developments in water sources with the transformations of the oasis environment.The study relied on the descriptive analytical approach, describing and evaluating the developments experienced by the domestic water dipper, and monitoring the constraints it faces. Based on the data of the official sources, the technique of participatory observation and field interviews. In addition, the “Sasplanet” program was also used to track the depth of the domestic water sources, and to analyse field data using the statistical, cartographic and iconographic expressions. The study found that the sources of domestic water in rural center of the oasis of Mezkita, witnessed quantitative and qualitative changes, contributed by the climate of the region and the interventions of local actors in the management of Moroccan water in rural areas. The latter resulted in immediate constraints linked to developments in the domestic water component, such as changing lifestyles, poor sewage management, poor quality of the connection network and a decline in water depth.
Keywords: Mezkita Oasis; Domestic Water; Management; Transformations; Sources of Domestic Water; Management Constraints